Income-Dependent Punitive Damages - Ronen Perry; Elena Kantorowicz-Reznichenko (Washington University Law Review, 2018)
The Article unfolds in six parts. Part I outlines the development of the law governing punitive damages. Part II analyzes the possible rationales for this unique “middle-ground” doctrine, focusing on deterrence and retribution. Part III considers whether the defendant’s wealth should be considered in assessing punitive damages in light of their underlying goals. Part IV demonstrates how the defendant’s wealth can be integrated into the calculation. It extracts the foundations from European criminal justice systems and adapts the model to American civil law. Part V defends the proposed model from the relevant theoretical perspectives. Lastly, Part VI discusses potential hurdles to the implementation of the new model—constitutional constraints, statutory caps on punitive damages, and the need for special procedural tools.
Keywords: Damages; Punitive; Compensatory; Tort; Income; Common Law; Constitutional Constrains; Excessive Fines; Eighth Amendment; Due Process; Fourteenth Amendment; Deterrence; Retribution; Statutory cap; Disgorgement; Tort Law; Criminal Law; International Criminal Law; Monetary Sanction; Income Dependent